An Evaluation of Information Sources Regarding Drug Use and/or Poisoning Cases of Community Pharmacists in Ankara, Turkey - Çeliker, Ayçe; Kara, Emre; Karahan, Sevilay (Acta Medica, 2021)
Objective: Exploring and categorizing the drug and/or poisoning information resources available in community pharmacies in Ankara according to some variables, and revealing common opinions regarding the future of the profession and information resources. Materials and Methods: This study was conducted as an online questionnaire for community pharmacists in Ankara. It had four headings on the pharmacists’ demographics, their general information resources, specific resources in specific topics, and 4 suggestions regarding the future of pharmacy and drug information resources. Results: The number of participants was 134 as 17.9% of 746 e-mail addresses. Mean ages±standart deviation were 40.9±12.0 years. The top 3 information sources on poisonings were the internet, colleagues, and physicians with 74.6%, 43.3%, and 30.6%, respectively. Participants in the “colleagues” group in terms of poisoning preferences had a shorter period after graduation (p=0.001). In the drug information inquiries package inserts, internet and colleagues were preferred mostly, with 69.4%, 63.4%, and 35.8%, respectively. Age groups and graduation years were statistically different regarding the “package inserts” and “colleagues” groups (p=0.012 and p=0.001, and p=0.019 and p<0.001, respectively). The most “totally agreed” suggestion was accepting the pharmacies’ being important drug and/or poison information resources for consumers with 68.7%. Conclusion: The pharmacists have been fulfilling their duty of “being an information resource” through rather limited resources. To equip community pharmacists properly, authorities, professional institutions, and universities need to contribute to the process in different ways together with pharmacists being aware of their responsibilities.